PERANCANGAN VIRTUAL PRIVATE NETWORK (VPN) DENGAN MENGGUNAKAN LINUX CLEAR OS 6.0 DI DINAS KOMINFO-SP PROVINSI BANTEN - Saleh Dwiyatno; Dwi Sumarto; Mohamad Nasir (Teknik Informatika Fakultas Ilmu Komputer, 2019)
Increasingly advanced technological developments affect a system and efficiency in the world of work. Because it is very much needed by the internet network, especially the IT division, besides the importance of the internet network, companies or agencies really need a private network (VPN) as a limitation on the use of internet connections. The absence of a private network and the limitation of internet usage of a company can be disrupted. To overcome this, the writer will design a VPN by using Clear OS 6.0. VPN is one of the facilities available on the Clear OS server that allows IT workers to access the office's internal network using private network connections from inside or outside the agency. From the results of the research, the author has proven that Clear OS can filter identification of devices based on IP Address and selectivity of data service requests based on the website address visited.